Randomized Controlled Study to Evaluate Microbial Ecological Effects of CPP-ACP and Cranberry on Dental Plaque. (April 2020) - Philip, N.; Leishman, S.J.; Bandara, H.M.H.N.; Healey, D.L.; Walsh, L.J.
Introduction: Ecological approaches to dental caries prevention play a key role in attaining long-term control over the disease and maintaining a symbiotic oral microbiome. Objectives: This study aimed to investigate the microbial ecological effects of 2 interventional dentifrices: a casein phosphopeptide–amorphous calcium phosphate (CPP-ACP) dentifrice and the same dentifrice supplemented with a polyphenol-rich cranberry extract. Methods: The interventional toothpastes were compared with each other and with an active control fluoride dentifrice in a double-blinded randomized controlled trial. Real-time quantitative polymerase chain reaction (qPCR) analysis was used to determine changes in the bacterial loads of 14 key bacterial species (8 caries associated and 6 health associated) in the dental plaque of trial participants after they used the dentifrices for 5 to 6 wk. Results: From the baseline to the recall visit, significant differences were observed between the treatment groups in the bacterial loads of 2 caries-associated bacterial species ( Streptococcus mutans [ P < 0.001] and Veillonella parvula [ P < 0.001]) and 3 health-associated bacterial species ( Corynebacterium durum [P = 0.008], Neisseria flavescens [ P = 0.005], and Streptococcus sanguinis [ P < 0.001]). Compared to the fluoride control dentifrice, the CPP-ACP dentifrice demonstrated significant differences for S. mutans ( P = 0.032), C. durum ( P = 0.007), and S. sanguinis ( P < 0.001), while combination CPP-ACP–cranberry dentifrice showed significant differences for S. mutans ( P < 0.001), V. parvula ( P < 0.001), N. flavescens ( P = 0.003), and S. sanguinis ( P < 0.001). However, no significant differences were observed in the bacterial load comparisons between the CPP-ACP and combination dentifrices for any of the targeted bacterial species ( P > 0.05). Conclusions: Overall, the results indicate that dentifrices containing CPP-ACP and polyphenol-rich cranberry extracts can influence a species-level shift in the ecology of the oral microbiome, resulting in a microbial community less associated with dental caries (Australian New Zealand Clinical Trial Registry ANZCTR 12618000095268). Knowledge Transfer Statement: The results of this randomized controlled trial indicate that dentifrices containing casein phosphopeptide–amorphous calcium phosphate (CPP-ACP) and polyphenol-rich cranberry extracts were able to beneficially modulate the microbial ecology of dental plaque in a group of high caries-risk patients. This could contribute toward lowering the risk of developing new caries lesions, an important goal sought by patients, clinicians, and policy makers.